2014
DOI: 10.1007/s13277-014-2108-5
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the role of MCL1 in tumorigenesis of solid cancer: gene expression correlates with antiproliferative phenotype in breast cancer cells and its functional regulatory variants are associated with reduced cancer susceptibility

Abstract: Compared to the well-defined anti-apoptotic role of myeloid cell leukemia sequence 1 (MCL1), its antiproliferative function in tumorigenesis is less studied. We had recently reported that regulatory variants of MCL1 contribute to enhanced promoter activity but reduced risk of lung cancer. We hypothesized that MCL1 expression may manifest antiproliferative phenotype and its functional variations may have etiological relevance for breast cancer. We manipulated MCL1 expression in MCF-7 cells and MDA231 with overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…We confirmed this hypothesis using both cell growth studies and the Cell-Trace™ Violet dye dilution assay. This observation synergizes with prior studies that have highlighted the role of MCL1 in regulating apoptosis during the cell cycle, especially during mitosis 51,53,[57][58][59] . Our results suggest that having a sufficient amount of free MCL1, indicative of a non-apoptotic state, can promote cell growth and may aid in insuring that there is sufficient MCL1 to enable exit from mitosis once the cell cycle is complete.…”
Section: Discussionsupporting
confidence: 87%
“…We confirmed this hypothesis using both cell growth studies and the Cell-Trace™ Violet dye dilution assay. This observation synergizes with prior studies that have highlighted the role of MCL1 in regulating apoptosis during the cell cycle, especially during mitosis 51,53,[57][58][59] . Our results suggest that having a sufficient amount of free MCL1, indicative of a non-apoptotic state, can promote cell growth and may aid in insuring that there is sufficient MCL1 to enable exit from mitosis once the cell cycle is complete.…”
Section: Discussionsupporting
confidence: 87%
“…MCL1 gene expression was thought to be significantly associated with chemo- and radio-resistance and poor prognosis among NSCLC patients [ 25 ]. In contrast, several studies have indicated that MCL1 overexpression was a protective factor against breast cancer and can reduce tumor cell proliferation and arrest cell cycle progression [ 26 ]. Due to the small sample size of patients and insufficient sequencing depth in the present study, we cannot draw a sound conclusion that MCL1 contributes to the different outcomes of the patients with two distinct genotypes.…”
Section: Discussionmentioning
confidence: 99%